The Influence of Helium And Cavitation on the Yeast Life Process - Коval , І. Z. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2021)
Purpose of the study is to іnvestigate the simultaneous effect of cavitation and helium on the viability of yeast of the genus Saccharomyces cerevisiae in water. To study the change in the number of cells during cavitation treatment of the water system in the gas atmosphere.Methods. Yeast of Saccharomyces cerevisiae type were used as test microorganisms. Freshly prepared distilled desaerated water was used for the research, to which yeast cells were introduced with a microbiological loop. The volume of the model medium was cooled in a glass reactor with tap water, the temperature of which corresponded to 298 ± 1 K. The total duration of the process was 2 hours. The cavitation source was an ultrasonic generator UZDN-2T with frequency of 22 kHz and power of 35 W. The test water was bubbled with gas throughout the process. The test gas was helium. The number of microorganisms per unit volume of test water was determined by the total number of colonies on the nutrient medium on Petri dishes and expressed in colony-forming units (CFU).Results. In the experimental part of the work the process of water treatment with the content of yeast cells under cavitation conditions with simultaneous supply of helium is proposed. The efficiency of water purification from yeast as a result of the combined action of helium/cavitation has been established. The value of the effective rate constant of microorganisms destruction according to the kinetic reaction equation of the first order is calculated. The viability of yeast under cavitation conditions and bubbling of helium through the water system has been studied. The proportion of destroyed cells during the two-hour action of yeast-contaminated water at different treatment regimes was calculated and compared. An active decrease in the number of Saccharomyces cerevisiae in the aqueous medium at the beginning of the process with the achievement of the proportion of destroyed cells (Dd) 40.48% after 30 min of combined He/cavitation action at the initial microbiological water contamination of 4.2 · 103 CFU/cm3. NMend = 100 CFU/cm3 after 90 minutes of water treatment, that corresponds to the water purification degree > 97%. The end result is almost pure water, which allows to discharge treated water into natural water.Conclusions. The obtained results indicate intensive cavitation purification of water from the studied microorganisms in the experimental conditions. The influence of the studied gas nature on the process of destruction of microbiological contaminants in water is described.